Press Offices in institutions and companies. Information versus Public Relations - Moya Hiniesta, Fernando (2013)
The work of the press offices in institutions and enterprises, the substitution of sources of information and the operating mode in press releases, press conferences, etc., and generally all previous and subsequent work to ensure informative success, are detailed by linking them to a higher organizational communication. All this from the theoretical perspective and professional praxis, told with vivid, and historical, examples, and in which no less important is the work of anonymity in which are located, as authors of the released issues, the people in charge of these devices. Other aspects specific to the press offices are also discussed, beyond the tasks associated with writing reports, but of equal interest to public and private entities. And singularly the role they play in political campaigns.